Proceedings of the 2015 Annual Conference on Genetic and Evolutionary Computation 2015
DOI: 10.1145/2739480.2754638
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Regular Objectives for Blocking Permutation Flow Shop Scheduling

Abstract: The objective of this work is to present and evaluate metaheuristics for the blocking permutation flow shop scheduling problem subject to regular objectives. The blocking problem is known to be NP-hard with more than two machines. We assess the difficulty level of this problem by developing two population-based meta-heuristics: Genetic Algorithm and Artificial Bee Colony algorithm. The final goal is to measure the performance of these proposed techniques and potentially contribute in possible improvements in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Under C max criterion, an effective Revised Artificial Immune Systems (RAIS) algorithm is proposed in [23], a three-phase algorithm presented in [24], and a Discrete Particle Swarm Optimization algorithm (DPSO) with self-adaptive diversity control was treated in [25]. Subsequently, we refer to the Memetic Algorithm (MA) in [26], the Iterated Local Search algorithm (ILS) coupled with a Variable Neighborhood Search (VNS) in [27], and the Blocking Genetic Algorithm (BGA) and Blocking Artificial Bee Colony (BABC) algorithms in [28]. Experimental results demonstrated that both of the two later proposed algorithms are more efficient in finding better solutions than all other leading techniques.…”
Section: Problem Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Under C max criterion, an effective Revised Artificial Immune Systems (RAIS) algorithm is proposed in [23], a three-phase algorithm presented in [24], and a Discrete Particle Swarm Optimization algorithm (DPSO) with self-adaptive diversity control was treated in [25]. Subsequently, we refer to the Memetic Algorithm (MA) in [26], the Iterated Local Search algorithm (ILS) coupled with a Variable Neighborhood Search (VNS) in [27], and the Blocking Genetic Algorithm (BGA) and Blocking Artificial Bee Colony (BABC) algorithms in [28]. Experimental results demonstrated that both of the two later proposed algorithms are more efficient in finding better solutions than all other leading techniques.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…To generate the initial solution we have used the PF-NEH(x) heuristic as in [28]. However, instead of generating x solutions at the end of the heuristic we choose only the permutation with the minimum objective value.…”
Section: A Initial Solutionmentioning
confidence: 99%
See 2 more Smart Citations